2009
DOI: 10.1103/physrevb.79.085120
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the limits of the self-consistent Born approximation for inelastic electronic transport

Abstract: The non equilibrium Green function formalism is today the standard computational method for describing elastic transport in molecular devices. This can be extended to include inelastic scattering by the so called self-consistent Born approximation (SCBA), where the interaction of the electrons with the vibrations of the molecule is assumed to be weak and it is treated perturbatively. The validity of such an assumption and therefore of the SCBA is difficult to establish with certainty. In this work we explore t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 47 publications
0
35
0
4
Order By: Relevance
“…Also, very recent studies have shown that self-consistent Φ-derivable approximations can converge to unphysical solutions; [34][35][36][37][38][39][40][41][42][43][44]47,48 similar issues have been noted in the context of time-dependent simulations [40][41][42][43][44][47][48][49] using the Kadanoff-Baym equations, but can be remedied by introducing self-consistent contributions in controlled fashion. 43 Nevertheless, the use of self-consistent MBPT may be justified to some extent.…”
Section: 23mentioning
confidence: 97%
See 1 more Smart Citation
“…Also, very recent studies have shown that self-consistent Φ-derivable approximations can converge to unphysical solutions; [34][35][36][37][38][39][40][41][42][43][44]47,48 similar issues have been noted in the context of time-dependent simulations [40][41][42][43][44][47][48][49] using the Kadanoff-Baym equations, but can be remedied by introducing self-consistent contributions in controlled fashion. 43 Nevertheless, the use of self-consistent MBPT may be justified to some extent.…”
Section: 23mentioning
confidence: 97%
“…1 are retained while the Hartree diagrams are neglected. 34 In applications one also often neglects the real part of the electron-phonon Fock diagram. 74 These approximations work under the assumption of small polaron shifts.…”
Section: 213473mentioning
confidence: 99%
“…2(a) are equivalent to the so-called self-consistent Born approximation (SCBA) for the electronic self-energy considered in problems like e-ph interacting systems. [38][39][40][41][43][44][45][46][47] However, in the case of e-m interaction, one has to introduce additional bookkeeping in such diagrams to account for flipping of electron spin together with magnon emission or absorption, as illustrated in Fig. 2.…”
mentioning
confidence: 99%
“…We note that in SCBA for e-ph interacting systems, Σ H is often neglected 41,46 due to being small and, therefore, having little effect on the final current (this becomes unwarranted for larger e-ph interaction strengths where SCBA breaks down 46 ). For the e-m interacting systems, the situation is much more complex because direct evaluation of Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation